2018
DOI: 10.1029/2018wr022585
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion and Mixing in Three‐Dimensional Discrete Fracture Networks: Nonlinear Interplay Between Structural and Hydraulic Heterogeneity

Abstract: We investigate the relative impact of topological, geometric, and hydraulic heterogeneity on transport processes in three-dimensional fracture networks. Focusing on the two largest scales of heterogeneity in these systems, individual fracture and network structure, we compare transport through analogous structured and disordered three-dimensional fracture networks with varying degrees of hydraulic heterogeneity. For the moderate levels of hydraulic heterogeneity we consider, network structure is the dominant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 60 publications
1
41
0
Order By: Relevance
“…For every fracture that intersects the inflow boundary an edge is added between the vertex in the graph corresponding to that fracture and the vertex representing the inflow boundary; likewise for the outflow boundary. Similar graph theoretical approaches have been used for a variety of studies concerning DFN including topological characterization (Andresen et al, ; Huseby et al, ; Hope et al, ; Hyman & Jiménez‐Martínez, ) and backbone identification (Hyman et al, ; Valera et al, ). The utility of a graph theoretical approach is that topological properties of the networks can be queried and characterized in a formal mathematical framework.…”
Section: Flow and Transport Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For every fracture that intersects the inflow boundary an edge is added between the vertex in the graph corresponding to that fracture and the vertex representing the inflow boundary; likewise for the outflow boundary. Similar graph theoretical approaches have been used for a variety of studies concerning DFN including topological characterization (Andresen et al, ; Huseby et al, ; Hope et al, ; Hyman & Jiménez‐Martínez, ) and backbone identification (Hyman et al, ; Valera et al, ). The utility of a graph theoretical approach is that topological properties of the networks can be queried and characterized in a formal mathematical framework.…”
Section: Flow and Transport Simulationsmentioning
confidence: 99%
“…In a fracture network, larger features can play a more dominant role than in-fracture aperture variability in determining the structure of the fluid velocity field (Bisdom et al, 2016;de Dreuzy et al, 2012;Karra et al, 2015;Makedonska et al, 2016). While it is understood that macroscale network traits influence the arrangement of the fluid flow field within a fracture network (Edery et al, 2016;Hyman & Jiménez-Martínez, 2018), a direct link between geometric and topological properties of the fracture network and upscaled transport observables is still lacking. With such a wide range of relevant length scales, several orders of magnitude (Bonnet et al, 2001;Davy et al, 2013;Hardebol et al, 2015), it is challenging to identify which features of a fracture network influence which flow and transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…Each set contains 10 networks composed of uniformly sized square fractures with edge lengths of 1 m within cuboid domain with dimensions of 20 m × 10 m × 10 m. Note that power law tails in advective travel time distributions does not require a power law distribution of fracture lengths (Hyman and Jiménez-Martínez, 2018;Painter et al, 2002). Each set contains 10 networks composed of uniformly sized square fractures with edge lengths of 1 m within cuboid domain with dimensions of 20 m × 10 m × 10 m. Note that power law tails in advective travel time distributions does not require a power law distribution of fracture lengths (Hyman and Jiménez-Martínez, 2018;Painter et al, 2002).…”
Section: Discrete Fracture Network Simulations: Particle Travel Time mentioning
confidence: 99%
“…Sævik and Nixon () included topological properties of two‐dimensional fracture networks into analytic expressions for permeability to account for network structure. Hyman and Jiménez‐Marttínez () used this graph representation to aid in the investigation of the relative impact of connectivity, geometric, and hydraulic heterogeneity on transport processes. Santiago et al, (, , ) proposed a method of topological analysis that measured centrality properties of nodes in the graph, which describes characteristics such as the number of shortest paths through a given node.…”
Section: Topological Inquiriesmentioning
confidence: 99%
“…In the second, each intersection between fractures is represented by a vertex and fractures are represented by a collection of edges. Hyman et al (2018) recently provided a rigorous mathematical exposition of these graph representations and showed that they are projections of a more general bipartite graph representation. Then we demonstrate the utility of the proposed method by using these graph representations to efficiently reproduce various features of the breakthrough curve, for example, first arrival, peak arrival, and scaling behavior in the tail.…”
Section: Introductionmentioning
confidence: 99%